Interactions among Sustainable Development Goals: Knowledge for identifying multipliers and virtuous cycles. (4th June 2020) - Pham‐Truffert, Myriam; Metz, Florence; Fischer, Manuel; Rueff, Henri; Messerli, Peter
Abstract: Developed to be interconnected by design, the 17 sustainable development goals (SDGs) and their 169 targets have attracted a growing scientific community committed to exploring the systemic interactions inherent to the 2030 Agenda. Understanding which SDGs influence one another (positively or negatively) is critical to prioritize and implement policies that maximize synergies between goals while navigating trade‐offs. In this way, the need for informed decision‐making urgently requires knowledge of context‐specific SDG interactions. Drawing on an extensive literature review (including scientific reports and scholarly articles), we collected, synthesized, and analyzed data about negative and positive interactions among SDG goals and targets. Based on this unique dataset, our analysis focused on three key elements of the resulting network of SDG interactions: First, we identified the most dominant SDGs in the network. Second, we identified systemic multipliers, defined as nodes with higher weighted amounts of outgoing than incoming influence. Third, we identified critical sub‐networks of strongly interconnected SDG targets, highlighting possible virtuous cycles that could serve as concrete entry points to realize the 2030 Agenda. Building on our results, a collaborative effort to add and refine data on behalf of an open‐knowledge platform could provide a solid basis for further analysis and enhanced usability in concrete contexts.